Pemberdayaan Siswa dalam Peningkatan Pengetahuan Mengenai Konsep Arimatika - Alberth Supriyanto Manurung; Abdul Halim (Abdimas Mandalika, 2022)
Abstract:  This community service activity is carried out with the aim of increasing knowledge through the concept of arithmetic, which is to increase knowledge which changes every time. The subjects of this community service are 30 students at SDN Jakarta. The activity begins with preparations in the form of socialization at the location where the activity will be carried out to provide an explanation of the activities to be carried out. At the stage of implementing the activity, students are gathered in a room to listen to the presentation of material on the concept of arithmetic, then the implementing team conducts counseling and demonstrations about arithmetic material followed by the best way to work on the questions. The instructor conducts an evaluation in the form of questions and answers to participants during the counseling. Based on the evaluation of activities, there has been an increase in knowledge about arithmetic material, after counseling and demonstration students have been carried out on how to solve arithmetic material problems correctly. Students who have knowledge of arithmetic concepts increased from being able to answer 5 questions from 15 questions to 10 questions from 15 questions with an increase in answering questions above 60%. Furthermore, we as the implementing team suggest that regular counseling actions be carried out both to different targets, namely students who have not received counseling, as well as the same target for refreshment and re-evaluation. Counseling or training also needs to be carried out with teacher targets, so that trained teachers can convey back to their students.Abstrak: Kegiatan pengabdian masyarakat ini dilaksanakan dengan tujuan untuk meningkatan pengetahuan melalui konsep arimatika adalah untuk menambah ilmu pngetahuan yang tiap waktu mengalami perubahan. Subjek pengabdian kepada masyarakat  ini adalah 30 siswa siswi di SDN Jakarta. Kegiatan diawali dengan persiapan berupa sosialisasi di lokasi yang akan dilakukan kegiatan untuk memberikan penjelasan tentang kegiatan yang akan dilakukan. Pada tahap pelaksanaan kegiatan, siswa dikumpulkan dalam suatu ruangan untuk mendengarkan pemaparan materi mengenai konsep arimatika, Kemudian  tim pelaksana melakukan penyuluhan dan demonstrasi tentang materi arimatika. Penyuluh melakukan evaluasi berupa tanya jawab kepada peserta selama penyuluhan. Berdasarkan evaluasi kegiatan, telah terjadi peningkatan pengetahuan tentang materi arimatika, siswa-siswi setelah dilakukan penyuluhan dan demonstrasi mengenai cara menyelesaikan soal materi arimatika dengan benar. Siswa yang memiliki pengetahuan tentang konsep arimatika meningkat dari yang awalnya mampu menjawab 5 soal dari 15 soal menjadi 10 soal dari 15 soal dengan peningkatan menjawab soal diatas 60%. Selanjutnya, kami sebagai tim pelaksana menyarankan agar dilakukan tindakan penyuluhan secara rutin baik kepada sasaran yang berbeda yaitu siswa yang belum mendapatkan penyuluhan, maupun sasaran yang sama untuk penyegaran dan evaluasi ulang. Penyuluhan atau pelatihan juga perlu dilakukan dengan sasaran guru, agar para guru yang terlatih dapat menyampaikan kembali kepada siswanya.